A randomized study of comparison between Intravenous infusion of 0.5 mcg/kg of clonidine and 1 mcg/kg of clonidine on hemodynamic stress response to pnuemo peritoneum and intubation response during laparoscopic surgeries in a tertiary care hospital in a sub urban population - Sindhuja Somasundaram,; Selvakumaran Pannirselvam, (Asian Journal of Medical Sciences, 2022)
Background: The laparoscopic surgical procedure has made remarkable changes in the surgical field. Conditions, such as pneumoperitoneum, has an impact on several homeostatic systems. To prevent them, different anesthetic techniques such as general anesthesia, spinal, intra dural, epidural, and at times combination of different techniques were used, Clonidine has various beneficial effects during the perioperative period, and they improve hemodynamic stability in response to intubation and surgical stress. Aims and Objectives: The present study was to investigate that the randomized study of comparison between Intravenous infusion of 0.5 mcg/kg of Clonidine and 1 mcg/kg of Clonidine on hemodynamic stress response to pnuemoperitoneum and intubation response during laparoscopic surgeries in a tertiary care hospital in a sub urban population. Materials and Methods: This study was conducted as a randomized single-blinded control trail to compare Intravenous infusion of 0.5 mcg/kg of Clonidine and 1mcg/kg of Clonidine on hemodynamic stress response to pneumoperitoneum and intubation response during laparoscopic surgeries. Results: Post-operative pain score in the Clonidine 1 mcg/kg group was found to be significantly lower compared to Clonidine 0.5 mcg/kg group and hemodynamic parameters such as pulse rate, systolic blood pressure, diastolic blood pressure, mean arterial pressure, and saturation levels were slightly lower in the group which was administered with Clonidine 1 mcg/kg compared to the other group which received Clonidine 0.5 mcg/kg however. Conclusion: The study highlights the importance of delivery of clonidine 1 mcg/kg facilities better outcomes in laparoscopic surgeries with lesser post-operative pain and lesser disturbance in hemodynamic parameters.